Stability issues in German money multiplier forecasts - Rainer Polster; Andreas Gottschling (Deutsche Bank Research, 1999)
This paper investigates the stability of the German money supply focusing on the period 1991 - 1998. It is shown that the standard ARIMA-Transfer model approach in the literature needs to be augmented by a cointegration term to adequately model the dynamics of money supply in Germany. Additional analysis with regard to the influence of financial innovations on the control of money supply yields evidence that the influence of financial innovations on the multiplier has increased steadily during the observation period.
Keywords: E4; E5; 330; Money Supply; Financial Innovation; Forecasting Money Multiplier; Geldschöpfung; Geldangebot; Volatilität; Finanzinnovation; ARCH-Modell; Schätzung; Deutschland